2012 Global Hunger Index Data - von Grebmer, Klaus; Ringler, Claudia; Rosegrant, Mark W.; Olofinbiyi, Tolulope; Wiesmann, Doris; Fritschel, Heidi; Badiane, Ousmane; Torero, Maximo; Yohannes, Yisehac; Thompson, Jennifer; von Oppeln, Constanze; Rahall, Joseph (International Food Policy Research Institute, 2012)
The 2012 GHI report focuses particularly on the issue of how to ensure sustainable food security under conditions of water, land, and energy stress. Demographic changes, rising incomes and associated consumption patterns, and climate change, alongside persistent poverty and inadequate policies and institutions, are all placing serious pressure on natural resources. In this report, IFPRI describes the evidence on land, water, and energy scarcity in developing countries and offers two visions of a future global food system—an unsustainable scenario in which current trends in resource use continue, and a sustainable scenario in which access to food, modern energy, and clean water improves significantly and ecosystem degradation is halted or reversed. Concern Worldwide and Welthungerhilfe provide on-the-ground perspectives on the issues of land tenure and title as well as the impacts of scarce land, water, and energy on poor people in Sierra Leone and Tanzania and describe the work of their organizations in helping to alleviate these impacts.